Pendidikan Karakter dan Moralitas Dalam Ajaran Catur Guru - Yuliandari, NI Putu Silvia; Dharman Gunawan, I Gede; Jatiyasa, I Wayan; Sariani Binawati, Ni Wayan; Diatmika, I Dewa Gede Ngurah (Jayapangus Press, 2023)
The concept of catur guru learning through education has a huge impact on student character and learning outcomes, because it can increase obedience in its full sense, and will create a life of mutual respect, balance and obedience. The character of each individual in the catur guru teaching plays an important role in the educational step. This study aims to determine character education and morality in catur guru teachings. The method used is qualitative research. The type of data used is qualitative data with a descriptive approach. The results of the study show that character education is very important to implement, everyone in the education system must be involved in its development. Policy is the main role model in this area. This is also emphasized in the teachings of Hinduism. Teachers play an important role in classroom learning by interacting with students.